An Analysis of Semantic Errors in Iraqi EFL Learners’ Writings - Leena Lafta Jassim (University of Thi-Qar Journal, 2019)
This study aims at presenting a comprehensive taxonomy capable of accounting for Iraqi EFL students’ semantic errors. It examines the types of these errors produced by third-year Iraqi EFL students in English Dep. in Education college for Human Science at Thi-Qar University. The recent study aims to classify and quantify the types of semantic errors made by Iraqi EFL students .Also it attempts to indicate the possible causes of these errors. The first hypothesis of this study is the most Iraqi EFL students fall in the errors of confusion of sense relations. The second hypothesis is that the minimal or incomplete knowledge of Iraqi EFL students for English diction is the main factor to fall in many types of semantic errors . The results of the analysis of ninety-four essays collected from Ninety-four students in class are analyzed and statistically indicated .The findings indicate that confusion of sense relations errors were more common than stylistic ones; 65.89% compared with 14.05%. The researcher also discusses the pedagogical implications for the teaching of vocabulary for foreign language learners.